Abbreviations in Slang Language Used by Gen Z Tik Tok Influencers of Indonesia - ihwans, yudi (BRIN Publishing (Penerbit BRIN), 2024)
ABSTRAK The study of abbreviations in the slang language used by TikTok influencers from Gen Z examines the use of abbreviations in the slang language adopted by TikTok influencers from this generation. The main issue addressed in this research is how slang language abbreviations serve as an effective communication tool while simultaneously shaping group identity on social media. The purpose of this study is to describe the forms of abbreviations in the slang language used by TikTok influencers from Gen Z on the accounts @fujiiian, @alwifahry, @hesfinatia, @iniganta, and @emilmario69. This research employs a qualitative descriptive method, with data collected in the form of screenshots and captions from TikTok video content within a specific period. The data analysis technique involves data reduction, data presentation, and drawing conclusions to identify patterns in the use of abbreviations. The results of this study reveal 52 forms of abbreviations categorized into three main types: acronyms, initialisms, and clippings. Acronyms are the most dominant category with 29 instances, followed by initialisms with 19 instances, and clippings with 4 instances. These findings indicate that abbreviations not only expedite communication but also serve as an expression of Gen Z identity. This research contributes to modern linguistic studies by highlighting the role of slang language in shaping communication patterns in a dynamic digital era. Keywords: abbreviation, slang language, TikTok, influencers, Gen Z.